2022
DOI: 10.1037/cou0000591
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Black adolescent males’ experiences with racism and internalized racial oppression.

Abstract: We explore Black male high school students’ perceptions of racial oppression, their internalization of racial oppression, and the impact of these experiences on their academic lives. Using constructivist grounded theory, 10 semi-structured interviews were conducted with Black adolescent boys. Results identified five core categories: (a) racial socialization, (b) understandings of and experiences with racism, (c) emotional and behavioral responses to racism, (d) internalization of racial oppression, and (e) sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…It is also notable that participants in the current study were limited to White participants; this decision was a matter of statistical power and is not intended to suggest that non-White police officers are not also capable of racial essentialist views, stereotyping, and incorrect decisions to use lethal force on Black suspects (Mbuba, 2018). Yet, I would argue that the mechanisms through which non-White police officers make biased decisions to use lethal force are likely to be quite different than White police officers, for example, they may include processes of racial conformity (Helms, 1995) and/or internalized racism based on their own experiences of racism (Bailey et al, 2021). Exploration of such processes would warrant a full sample of non-White participants, and would be a fruitful future direction for researchers.…”
Section: Discussionmentioning
confidence: 99%
“…It is also notable that participants in the current study were limited to White participants; this decision was a matter of statistical power and is not intended to suggest that non-White police officers are not also capable of racial essentialist views, stereotyping, and incorrect decisions to use lethal force on Black suspects (Mbuba, 2018). Yet, I would argue that the mechanisms through which non-White police officers make biased decisions to use lethal force are likely to be quite different than White police officers, for example, they may include processes of racial conformity (Helms, 1995) and/or internalized racism based on their own experiences of racism (Bailey et al, 2021). Exploration of such processes would warrant a full sample of non-White participants, and would be a fruitful future direction for researchers.…”
Section: Discussionmentioning
confidence: 99%
“…School counselors, therefore, should foster discussions of healthy CREID, not only as a means of healthy development generally, but also as a protective factor for students of color. Bailey et al (2022) offered important suggestions to school counselors engaging in conversations on racial identity. First and foremost, heightened awareness of the experiences of students of color is imperative for school counselors, especially regarding racism, racial socialization, and internalized oppression.…”
Section: Component 1: Racial Identity Developmentmentioning
confidence: 99%
“…Research consistently documents associations between internalized and interpersonal forms of stigma and mental health problems in multiple groups of stigmatized youth (e.g., youth of Color, girls, sexual minority youth; Bailey et al, 2021;Butler-Barnes et al, 2022;Chodzen et FUTURE DIRECTIONS IN STIGMA AND YOUTH MENTAL HEALTH TREATMENT 5 al., 2019;Price-Feeney et al, 2021;Reed et al, 2019;Rogers et al, 2022;Watson et al, 2019;Weeks & Sullivan, 2019). Relatively fewer studies have examined structural stigma in youth, but scholars have found associations between structural stigma and youth mental (e.g., anxiety, depression, suicidality; Beccia et al, 2022;Duncan & Hatzenbuehler, 2014;Hatzenbuehler, 2011;Hatzenbuehler & Keyes, 2013;Saewyc et al, 2020;Torres et al, 2018) and behavioral (e.g., smoking, alcohol/substance use; Eisenberg et al, 2020;Hatzenbuehler et al, , 2015Watson et al, 2020Watson et al, , 2021 health concerns.…”
Section: Future Directions In Mental Health Treatment With Stigmatize...mentioning
confidence: 99%